Is It Necessary to Fully Charge Your Electric Vehicle? - Claude Ziad El-Bayeh (17542284) (2021)
The transition of the transportation sector from internal combustion engine vehicles to battery electric vehicles (EVs) will heavily increase the energy demand on the network, causing severe techno-economic problems. To solve these issues, advanced charging strategies were proposed to reduce the EVs’ charging impact on the network. The problem arises when all EV-owners decide to fully charge their EVs at night even if they might not use the total charged energy the next day. Hence, even with the presence of advanced charging and control strategies, the problem of high penetration level of EVs might not be completely solved without the positive participation of the EV-owners. Some questions can be asked and need answers. Is it necessary to fully charge all EVs at night? What happens if fully charging the EVs is delayed to the next day? To answer these questions, this paper studies the impact of charging EVs to different State of Charge (SOC) levels on the network. Since controlling the charging of all EVs is difficult, a three-level charging strategy is developed that suggests the SOC threshold-limit for each EV, which guarantees the network’s operation within its maximum limits even with a 100% penetration level of EVs charging simultaneously. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3085244 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.